240 Hz OLED technology properties that can enable improved image quality. Issue 7 (20th January 2015) - Hoffman, David M.; Johnson, Paul V.; Kim, Joohwan S.; Vargas, Andy D.; Banks, Martin S.
Abstract Large screen Organic Light Emitting Diode (OLED) technology is finally emerging as a technology ready for consumer use. OLED has a number of areas in which it can in principle be better than Liquid Crystal Displays (LCDs); two ways in particular are that OLED technology can achieve black levels that are much darker than LCDs, and the OLED pixels can switch extremely rapidly. These differences can permit OLED displays to outperform LCD under a number of conventional scenarios, but it can also enable some dramatically improved stereoscopic 3D (s3D) displays, including full‐resolution temporal multiplexing with more than two views. In this paper, we review a set of experiments evaluating the strengths and weaknesses of OLED technology in general with a particular emphasis on understanding how the strengths of OLED technology can be leveraged to maximize the performance of an s3D display system.